Child labour in India: legal regulation - "Koninkar, Lingraj M." (New Delhi, 2014)
This book aims at clearly to understand the ground realities of the complex problem of child labour in socio-legal framework and to find out solutions. Problems of child labour with special reference to Gulbarga city in Karnataka is focused
Keywords: India--Gulbarga